The Development of Fantasy Teaching Materials by Using VAK (Visual Auditory Kinesthetic) on 7th Grade Students in SMP Negeri 1 Medan - Nurul Jamiah Rangkuti; Khairil Ansarif; Wisman Hadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to produce teaching materials by using VAK (Visual Auditory Kinestethic) on fantasy story material for 7th grade students of SMP Negeri 1 Medan. The research method used is Research and Development which refers to Borg and Gall model. The stages of development are the initial study phase, initial product development, and product trials. The results showed that the results of material validation included content eligibility with an average of 82% with a very good category, Eligibility for Presentation with an average of 87.5% with a very good category, and an assessment of language aspects with an average of 82.2% with a category very good. For the assessment of graphics by design experts obtained an average of 87% with the category "very good". Product trials are carried out in three stages: individual testing, small group trials, and limited field trials. Individual trials with an average of 86% with very good categories, small group trials with an average of 87.4% with very good categories, and limited field trials with an average of 88.3% with very good categories. The effectiveness of teaching materials is obtained through student learning outcomes in the pretest and posttest. Average score at pretest is 52 and at posttest is 76. This proves that the teaching material of fantasy story by using VAK (Visual Auditory Kinestethic) is feasible, easy, and effective for use in 7th grade students of SMP Negeri 1 Medan. This research has implications for Indonesian language learning process, which is teaching material by using VAK (Visual Auditory Kinestethic) which is developed to provide practical contributions, especially in the implementation of the learning process for teachers, teaching materials in the form of this module can be additional teaching materials to provide convenience in conveying fantasy story material taught, enriching and increasing students' knowledge about fantasy story so that learning will be more interesting and motivate students, trains students to learn independently.